Hormonal profile during the reproductive cycle and induced breeding of the dusky grouper Epinephelus marginatus (Teleostei: Serranidae) in captivity - Rodrigues-Filho, J. A. [UNESP]; Araújo, B. C.; Mello, P. H. [UNESP]; Garcia, C. E.O.; Silva, V. F.D.; Li, W.; Levavi-Sivan, B.; Moreira, R. G. [UNESP] (Elsevier, 2023)
Many fish species of interest in aquaculture, including the dusky grouper, Epinephelus marginatus, present reproductive dysfunctions due to confinement, which in turn affect the hypothalamus-pituitary-gonadal axis, which controls reproduction in vertebrates. The aim of this study is to use non-lethal tools to evaluate the reproductive activity of E. marginatus females in captivity. We measured the plasma profile of gonadal steroids and follicle-stimulating hormone (FSH) throughout 12 months and measured the oocyte's diameter. Additionally, we used human Chorionic Gonadotropin (hCG) and 17β-estradiol (E2) implants aiming to induce the vitellogenesis of non-vitellogenic females, and followed the plasma level of E2 and oocyte diameter. During the year, the concentration of the androgens testosterone (T) and 11-ketotestosterone (11-KT) did not change, while the plasma level of E2 significantly increased at the end of the cycle (September) compared with the first sampling month (October) in captivity. The plasma concentration of 17 α-hydroxyprogesterone (17α-OHP) was significantly higher in November than in May, June, July, and August, and it was also higher in October compared to May and June. Plasma FSH levels were higher in January compared to April, June, July, August, and September, and were lower in April compared to October, December, February, and March. However, these hormonal changes did not result in changes in the oocyte's diameter, which remained unchanged, at the stage of primary growth throughout the annual cycle. The induction of vitellogenesis with hCG did not change E2 levels, while the higher dose of E2 implants increased the plasma level of this estrogen after 30 days, but this alteration did not reflect in the diameter of oocytes and vitellogenesis was not triggered in both treatments. The data suggest that one of the reasons for the impaired vitellogenesis in E. marginatus in captivity can be related with the plasma FSH level, which does not stimulate enough synthesis of E2 to promote vitellogenesis. Moreover, hCG or E2, at the concentration used in this experiment, were not able to trigger vitellogenesis in animals in captivity, reinforcing the fact that environmental cues, which are not available in captivity, are imperative to the function of the hypothalamus-pituitary-gonadal reproductive axis in E. marginatus.
Keywords: Annual cycle; Gonadal steroids; Gonadotropins; Oocyte diameter; Vitellogenesis